(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted at the farm of Banghobondhu Shekh Mogibur Rahman Agriculture University, Gazipur during the period of November to December, 2010 to enhance the production of red amaranth (Amaranthus tricolor cv: BARI lal shak 1) through the improvement of growth and yield of red amaranth by optimizing the appropriate levels of nitrogen fertilizer. The experiment was laid out in a Randomized Complete Block Design (RCBD) comprising six treatments with four replication each. The treatment combinations were T0 (0 kg N ha-1), T1 (50 kg N ha-1), T2 (75 kg N ha-1), T3 (100 kg N ha-1), T4 (125 kg N ha-1) and T5 (150 kg N ha-1), respectively. Amounts of N, P, K and S applied from urea, TSP, MOP and gypsum were 68, 23, 17 and 4 kg ha-1, respectively. Data on plant height, leaf number, root-shoot growth and dry weight along with yield and BCR (benefit cost ratio) indicated that urea applied at the rate of 150 kg N ha-1 had a significant (p<0.01) effect on the short term growth and yield of red amaranth. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22047 J. Environ. Sci. & Natural Resources, 6(1): 99-102 2013